Why social entrepreneurship? Public and commercial, dual-approach for social enterprises with Chinese cases - Husheng Xu; Xiaoyan Song; Wei Song (International Journal of Management, Economics and Social Sciences (IJMESS), 2014)
Social entrepreneurship or enterprise is considered as an innovative form, which combines economic and social value creation to improve societal development. Theory and practice of this field are attracting more attention. In this article, we identified significant literature and journals as well as academic citation relationships for advancing scholarly research on social entrepreneurship. Then, we established a dual-approach for social entrepreneurship with China's cases: public and commercial, to illustrate the question why social entrepreneurship arises. At the end, future directions about legislation, contexts and performance were discussed.
Keywords: L33; M14; 330; Social Entrepreneurship/Enterprise; Public Approach; Commercial Approach; Non-profit; Social Mission; Resource and Opportunity